Report of the Working Group on Employment, Planning & Policy For the Twelfth Five Year Plan (2012-2017) - Planning Commission (Planning Commission, 2011)
A Working Group on Employment, Planning & Policy for the 12th Five Year Plan (2012-2017) was set up under the Steering Committee on Labour, Employment & Skill Development by the Planning Commission with Dr. Ashok Sahu, Principal Adviser (Labour, Employment & Manpower), Planning Commission, as the Chairman. The constitution of the Working Group and the Terms of Reference are given in Annexure-I. The Working Group subsequently co-opted Smt. Amarjeet Kaur, DDG, Ministry of Labour & Employment and Shri B.N. Nanda, DG, Labour Bureau as Members.
Government of India Labour, Employment & Manpower (LEM) Division
Government of India Labour, Employment & Manpower (LEM) Division